Use Coupon: CART10 and get 10% off on all online Study Material

Total Price: R

There are no items in this cart.
Continue Shopping
Get instant 50% OFF on Online Material.
Use coupon code: MOB50 | View Course list

f(x)=[x]+[-x] when xis not equal to 2 and A ,when X =2 if fx is continuous at x=2 thwn the value of A=?

3 years ago


Answers : (2)


Hi Koushik,


Ih you note

f(x) as x tends to 2 from the right ie 2+

f(2+) = 2-3 = -1

And f(x) as x tends to 2 from the left ie 2-

f(2-) = 1-2 = -1.


So f(2) = A = -1 for f(x) to be continuous at 2.


Hope it helps.

Wish you all the best.



Ashwin (IIT Madras).

3 years ago

For continuity lim x->2+ f(x) = f(2) = lim x-> 2-

Evalutaing left hand limit: 

When x->2-: [x]+[-x] = [2-h]+[-(2-h)] =1+[-2+h]=1-2=-1

Evaluating right hand limit

When x->2+ : [2+h]+[-2-h]= 2+(-3)= -1 

therefore f(2) = -1 to mk the function continuous

3 years ago

Post Your Answer

find the equation of a line passing through the point 3,2 and perpendicular to the line x=y
the line is y=5-x since the line is perpendicular to line y=x, the slope of this line is -1. and acc. to point slope formula i.e., (y-y’)=m(x-x’) hence (y-2)=(-1)(x-3) y-2=3-x y=5-x
Avani Patidar 2 months ago
draw the graph of sin(1/x).
the graph of sin -1 x is a curve with order pairs (0,0),(-1,1.5),(1,1.5) on
vivek 2 months ago
Prove that, If y = Sin -1 x, x ∈ (–1, 1) then dy/dx =1/√(1-x 2)
y = Sin -1 x ⇒ x = sin y dy/dx=cosy dy/dx=(dx/dy) -1 =1/cosy=1/ √(1-sin 2 y) =1/√(1-x 2 )
RAJU 27 days ago
y = Sin -1 x ⇒ x = sin y dy/dx=cosy dy/dx=(dx/dy) -1 =1/cosy=1/ √(1-sin 2 y) =1/√(1-x 2 )
Raghu Vamshi Hemadri 22 days ago
What is polar and pole of a circle?
a given circle , reciprocation in a circle means the transformation of each point in the plane into its polar line and each line in the plane into its pole .
how to calculte the determinant value of 2 rows and 3 col of values?
Hi student.. . . . Determinant is defined only for square matrices in which number of rows and columns is same. For the above case, determinant does not apply....
Harsh Patodia 11 months ago
=> x=y => x*x = y*x => x2 = yx => x2-y2 = yx- y2 => = y => x+y = y => y+y =y => 2y* 1 = y *1 => 2y / y = 1 => 2 =1 prove that this is wrong
x^2-y^2=yx-y^2 (x-y)(x+y)=y(x-y) x-y=0 since 0/0 is undefined u cant cut (x-y) on either side and therefore writting (x+y)=y is wrong
purva gupta 28 days ago
View all Questions »
More Questions On Differential Calculus

Ask Experts

Have any Question? Ask Experts

Post Question

Answer ‘n’ Earn
Attractive Gift
To Win!!!
Click Here for details